Application of adipose-derived mesenchymal stem cells in an in vivo model of peripheral nerve damage - González-Cubero, Elsa; González-Fernández, María Luisa; Rodríguez-Díaz, María; Palomo-Irigoyen, Marta; Woodhoo, Ashwin; Villar-Suárez, Vega (Frontiers in Cellular Neuroscience, 2022)
Background Neuropathic pain is one of the most difficult to treat chronic pain syndromes. It has significant effects on patients’ quality of life and substantially adds to the burden of direct and indirect medical costs. There is a critical need to improve therapies for peripheral nerve regeneration. The aim of this study is to address this issue by performing a detailed analysis of the therapeutic benefits of two treatment options: adipose tissue derived-mesenchymal stem cells (ASCs) and ASC-conditioned medium (CM). Methods To this end, we used an in vivo rat sciatic nerve damage model to investigate the molecular mechanisms involved in the myelinating capacity of ASCs and CM. Furthermore, effect of TNF and CM on Schwann cells (SCs) was evaluated. For our in vivo model, biomaterial surgical implants containing TNF were used to induce peripheral neuropathy in rats. Damaged nerves were also treated with either ASCs or CM and molecular methods were used to collect evidence of nerve regeneration. Post-operatively, rats were subjected to walking track analysis and their sciatic functional index was evaluated. Morphological data was gathered through transmission electron microscopy (TEM) of sciatic nerves harvested from the experimental rats. We also evaluated the effect of TNF on Schwann cells (SCs) in vitro. Genes and their correspondent proteins associated with nerve regeneration were analyzed by qPCR, western blot, and confocal microscopy. Results Our data suggests that both ASCs and CM are potentially beneficial treatments for promoting myelination and axonal regeneration. After TNF-induced nerve damage we observed an upregulation of c-Jun along with a downregulation of Krox-20 myelin-associated transcription factor. However, when CM was added to TNF-treated nerves the opposite effect occurred and also resulted in increased expression of myelin-related genes and their corresponding proteins. Conclusion Findings from our in vivo model showed that both ASCs and CM aided the regeneration of axonal myelin sheaths and the remodeling of peripheral nerve morphology.